Back Cover: Triisopropylsilylethynyl‐Functionalized Graphene‐Like Fragment Semiconductors: Synthesis, Crystal Packing, and Density Functional Theory Calculations (Chem. Eur. J. 52/2013). Issue 52 (23rd December 2013) - Zhang, Lei; Fonari, Alexandr; Zhang, Yue; Zhao, Guangyao; Coropceanu, Veaceslav; Hu, Wenping; Parkin, Sean; Brédas, Jean‐Luc; Briseno, Alejandro L.
<x xml:space="preserve">Abstract</x> Soluble graphene‐like fragment semiconductors with tri‐isopropylsilylethynyl groups, representing a family of model molecules for electronic devices, are synthesized and described by A. L. Briseno et al. in their Full Paper on page 17907 ff. There is a direct evolution of the π stacking arrangements by varying the geometric shape. These compounds easily form low‐dimensional charge‐transport systems. Density‐functional theory calculations were carried out to provide insights on how the molecular geometric shape influences the electronic structure and transport properties.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>